Improve Discoverability And Recognition For Your Research Activities With ORCID - Ksibi, Nabil (My University, 2021)
Persistent Identifiers (PIDs) are foundational components of research infrastructure. This session will offer an introduction to PIDs and how they enable trustworthy and transparent connections between researchers, their contributions and institutions. Researchers can use ORCID iDs to be uniquely identified and connected to their activities and contributions. Join this webinar to learn how to increase discoverability and recognition for your research with ORCID. There will be plenty of time for Q&A and we are looking forward to an interactive session and animated discussion.
Keywords: orcid; africarxiv; persistentidentifiers